The Influence Of Locus Of Control And Organizational Commitment On Employee Performance At The Regional Secretariat Of Lebong District - Nuriana Nuriana; Ida Angriani; M. Rahman Febliansa (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The purpose of this study was to determine locus of control and organizational commitment to employee performance at the Regional Secretariat of Lebong Regency. The sample in this study was 79 employees at the Regional Secretariat of Lebong Regency who had become civil servants. The sampling technique is a census. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The multiple regression results show a positive direction of regression with the equation Y = 8.641 + 0.312X1 + 0.492 X2. Locus of control has a significant effect on employee performance at the Regional Secretariat of Lebong Regency because the significant value is 0.001 less than 0.05. This illustrates the increasing locus of control, the employee's performance will also increase. Organizational commitment has a significant effect on employee performance at the Regional Secretariat of Lebong Regency because the significant value of 0.000 is less than 0.05. This illustrates that the increasing organizational commitment, employee performance will also increase. Locus of control and organizational commitment have a significant simultaneous influence on employee performance at the Regional Secretariat of Lebong Regency because a significant value of 0.000 is less than 0.05.